KAWASAN EKONOMI KHUSUS DAN PEMBANGUNAN EKONOMI REGIONAL: SEBUAH STUDI LITERATUR - Nurafni Irma Suryani; Ratu Eva Febriani (Universitas Bengkulu, 2019)
Special Economic Zones are very important for the progress of an area. SEZ is able to contribute to the regional economy and increase economic development by providing direct and indirect effects. The purpose of this study is to determine the impact of special economic zones on regional economic development. The object of this study is to explore the establish SEZ in Indonesia just only refer to two SEZs namely SEI Mangke and Tanjung Lesung. This research used literature study as a method. The results show that SEZ make the regional economy is starting to move towards a better direction. The role of two SEZs observed have different impact on regional economy, SEI Mangke has a positive impact on macroeconomy indicator such as reduced unemployment, reduced poverty and an increased economic growth rate in Simalungun Regency. Otherwise, Tanjung Lesung just has a positive impact on MSMEsKeywords: Unemployment, Poverty, Economic Growth, Pengembangan UMKM, SEZ Sei Mangke, SEZ Tanjung Lesung